Osteoporosis associated with gyrate atrophy: A case report - Ahmet, Isik; Serdar, Koca Suleyman (Springer, 2006)
Gyrate atrophy (GA) is a rare degenerative, hereditary disease characterized by markedly high serum ornithine levels resulting from the deficiency of ornithine-delta-amino transferase (OAT), a mitochondrial matrix enzyme. Hyperornithinaemia is accompanied by lysinuria and reduced lysine plasma levels in GA. Type I collagen is known to play a role in osteoporosis pathogenesis. Lysine has a role in cross ligament formation of type I collagen, a bone matrix element, and thus, in bone strength. Although the most common complaint in GA is visual problems, the disease may include muscle involvement, as well. Reduced physical activity resulting from muscle involvement and hypolysinemia in GA may lead to osteoporosis. However, there is no data in the literature concerning the relation between GA and osteoporosis. In this report a GA case with early osteoporosis, besides visual deterioration and muscular signs, is reported, and the relation between GA and osteoporosis is emphasized for the first time.
Keywords: Gyrate atrophy; Lysine; Ornithine; Osteoporosis; Type I collagen